Confronting Competition Investment Response and Constraints in Uganda - Reinikka, Ritva, 1955- 1955- (The World Bank, 1999)
November 1999 - While macroeconomic reforms are necessary, firms' investment response is likely to remain limited without an accompanying improvement in public sector performance. Investment rates in Uganda are similar to others in Africa - averaging slightly more than 10 percent annually, with a median value of just under 1 percent. But the country's profit rates are considerably lower. These results are consistent with the view that Ugandan firms display more confidence in the economy than their counterparts in other African countries. Thus, for given profit rates, Ugandan firms invest more. At the same time, increased competition (because of economic liberalization) has exerted pressure on firms to cut costs. Many of those costs are not under the firms' control, however, so their profits have suffered. Using firm-level data, Reinikka and Svensson identify and quantify a number of cost factors, including those associated with transport, corruption, and utility services. Several factors - including crime, erratic infrastructure services, and arbitrary tax administration - not only increase firms' operating costs but affect their perceptions of the risks of investing in (partly) irreversible capital. The empirical analysis suggests that firms - especially small firms - are liquidity-constrained in the sense that they invest only when sufficient internal funds are available. But given the firms' profit-capital ratio, it is hard to argue that the liquidity constraint is binding in most cases, even though the cost of capital is perceived as a problem. This paper - a joint product of Macroeconomics 2, Africa Region, and Public Economics and Macroeconomics and Growth, Development Research Group - is part of a larger effort in the Bank to study economic policy, public service delivery, and growth. The authors may be contacted at rreinikka@worldbank.org or jsvensson@worldbank.org